Anatomy Education of Medical Students During the COVID 19 Pandemic - Khasawneh,Ramada R (Sociedad Chilena de Anatomía, 2021)
SUMMARY: COVID-19 created extraordinary challenges to anatomy education and teaching practices, as the anatomists try to achieve best knowledge delivery level for their discipline, without the use of traditional teaching aids such as the cadavers and microscopic slides. The present study was conducted to collect medical students’ response and opinions regarding the pros and cons of online teaching vs traditional teaching. 2263 medical studentswere recruited from the first three academic years. A multiple choice close-ended questionnaire regarding their opinion about virtual teaching mode for the anatomy discipline during COVID-19 pandemic was designed and circulated via emails.The majority (78.12 %) of the students agreed that they missed their traditional anatomy learning mode. Moreover, (92.92 %) of the students missed their campus and the college social life. The students strongly felt there is a gap and difficulty in understanding the topics that required practicing and visual orientation such as dissections, models, microscopic slides which help them in better memorizing and recalling the anatomical terms. The lack of proper devices and the absence of high quality internet were among the top reported issues that negatively affect online learning. These results indicated that, compared with traditional methods of teachings, the online learning in the medical schools had relatively poor planning and required continuous and combined efforts in order to improve the quality of online teaching specially for anatomy discipline, which may be an essential response for any unforeseen situation such as the COVID-19 pandemic. We should look at the current situation as an opportunity to apply modern anatomy education approaches which may be a necessity at the present time, with huge accomplishments achieved in the information and online technology field.